Cutaneous Atrophy Following Corticosteroid Injections for Tendonitis: Report of Two Cases - Rebecca Colwell; Mitchell Gullickson; Jonathan Cutlan; Erik Stratman (JMIR Dermatology)
AbstractCutaneous atrophy resulting from corticosteroid injections for musculoskeletal indications is an underrecognized adverse effect among orthopedists and dermatologists. We present two cases of cutaneous atrophy following corticosteroid injections for wrist tendonitis. Patients presenting with cutaneous atrophy following orthopedic corticosteroid injections may be misdiagnosed with linear morphea, atrophoderma, or vascular disorders and receive unnecessary workups and delays in appropriate management. Dermatologists play an essential role in the evaluation of these patients.